Survey of Leg Muscle Strengh and Ability to Kick the Ball in Football Games at SSB Hasanuddin - Karim, Achmad (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This research is a descriptive type of research using a "Survey" research design. This study aims to determine; (1) How is the leg muscle strength of SSB Hasanuddin football school students. (1) How is the ability to kick a football game in SSB Hasanuddin football school students. The population is all SSB Hasanuddin football school students. The sample used was 20 people. The sampling technique is saturated sampling. The data analysis technique used is descriptive analysis. The results of the study showed that; 1) The leg muscle strength of SSB Hasanuddin football school students is in the moderate category with a percentage of 40.00%. 2) The ability to kick a football game in SSB Hasanuddin football school students is in the moderate category with a percentage of 45.00%